Hysteresis Direct Torque Control of Unity Voltage Ratio Indirect Matrix Converter for Variable-Speed Induction Motor Drive - Wahyu Cahyo Hidayat; Charles Ronald Harahap; FX Arinto Setyawan (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2026)
This paper evaluates the performance of a unity–voltage-transfer-ratio Indirect Matrix Converter (IMC) supplying a three-phase induction motor under hysteresis-based Direct Torque Control (DTC). The objective is to verify whether a unity-ratio IMC (previously validated only for passive loads) can operate reliably in variable-speed motor-drive applications. The main contribution is a comprehensive assessment of speed dynamics, torque-flux regulation, converter voltage behavior, and transient response when driving an 11-kW induction machine. A complete MATLAB/Simulink model is developed, incorporating an AC/AC boost stage, a current-source rectifier, a clamp and braking circuit, and a voltage-source inverter governed by hysteresis DTC with an outer-loop PI speed controller. The procedure involves no-load tests and step-load disturbances at multiple operating frequencies to evaluate steady-state performance and dynamic behavior. The results show that the IMC maintains a stable fictitious DC-link voltage, generates balanced output voltages, and achieves sinusoidal input currents with controllable power flow. The motor exhibits smooth acceleration, slip between 0 and 0.98%, and torque-recovery times of approximately 0.43-0.54 s after load perturbations. These findings demonstrate that the unity-ratio IMC is suitable for high-performance induction-motor drives and provide a foundation for future research on enhanced AC/AC converter topologies.